2020
DOI: 10.1016/j.fertnstert.2019.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte vitrification for fertility preservation in women with endometriosis: an observational study

Abstract: Objective: To describe the outcome of fertility preservation (FP) using vitrified oocytes in patients with endometriosis and to determine the impact of ovarian surgery. Design: Retrospective observational study. Setting: University-affiliated private in vitro fertilization (IVF) center. Patient(s): Four hundred and eighty-five women with endometriosis who underwent FP from January 2007 to July 2018. Intervention(s): Vitrification of metaphase II (MII) oocytes for future use. Main Outcome Measure(s): Oocyte sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 49 publications
2
85
0
1
Order By: Relevance
“…Fertility preservation is increasingly considered an alternative for patients diagnosed with endometriosis who are at risk of compromised ovarian reserve. The usefulness of oocyte vitrification for FP in women with endometriosis was recently demonstrated in a large study which also confirmed the impact of age, number of oocytes and egg survival on the cumulative live birth rate (Cobo et al, 2020). Furthermore, the study showed that young women achieved better outcomes when they had oocytes vitrified for FP prior to the excision of ovarian endometrioma.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Fertility preservation is increasingly considered an alternative for patients diagnosed with endometriosis who are at risk of compromised ovarian reserve. The usefulness of oocyte vitrification for FP in women with endometriosis was recently demonstrated in a large study which also confirmed the impact of age, number of oocytes and egg survival on the cumulative live birth rate (Cobo et al, 2020). Furthermore, the study showed that young women achieved better outcomes when they had oocytes vitrified for FP prior to the excision of ovarian endometrioma.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the study showed that young women achieved better outcomes when they had oocytes vitrified for FP prior to the excision of ovarian endometrioma. The number of oocytes retrieved, therefore the number of metaphase II (MII) available for vitrification, was lower in operated women (Cobo et al, 2020). The recognition of number of oocytes stored and patient age as key factors for success brings forth the question regarding the appropriate number of oocytes to vitrify.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research the fertility rate of 2014 taking as for dependent variable and other five independent variable like democracy, health, Economically view, education and political situation. Samari (2019) In the second stage of the dependent variable is taking from the fertility rate of 2013 same as independent variables in 2013 and in third stage taking the sum of dependent variable 2014 and 2013 and apply robust test (Phelippeau, Cazalis, & Koskas, 2019;Wu, Satmary, Peng, & Hui, 2020) Human development report, UNDP and World Bank 2015 data bases, Polity data scores data sheet, are the sources of data collection for all the indicators and variables of study (Cobo et al, 2020;Sciorio & Anderson, 2019;Tierney, 2020).…”
Section: Methodsmentioning
confidence: 99%